Molecular Studies of the Protein Complexes Involving Cis-Prenyltransferase in Guayule (Parthenium argentatum), an Alternative Rubber-Producing Plant - Lakusta, Adam M.; Kwon, Moonhyuk; Kwon, Eun-Joo G.; Stonebloom, Solomon; Scheller, Henrik V.; Ro, Dae-Kyun (Frontiers in Plant Science, 2019)
Guayule (Parthenium argentatum) is a perennial shrub in the Asteraceae family and synthesizes a high quality, hypoallergenic cis-1,4-polyisoprene (or natural rubber; NR). Despite its potential to be an alternative NR supplier, the enzymes for cis-polyisoprene biosynthesis have not been comprehensively studied in guayule. Recently, implications of the protein complex involving cis-prenyltransferases (CPTs) and CPT-Binding Proteins (CBPs) in NR biosynthesis were shown in lettuce and dandelion, but such protein complexes have yet to be examined in guayule. Here we identified four guayule genes – three PaCPTs (PaCPT1-3) and one PaCBP, whose protein products organize PaCPT/PaCBP complexes. Co-expression of both PaCBP and each of the PaCPTs could complemented the dolichol (a short cis-polyisoprene)-deficient yeast, whereas the individual expressions could not. Microsomes from the PaCPT/PaCBP-expressing yeast efficiently incorporated 14C-isopentenyl diphosphate into dehydrodolichyl diphosphates; however, NR with high molecular weight could not be synthesized in in vitro assays. Furthermore, co-immunoprecipitation and split-ubiquitin yeast 2-hybrid assays using PaCPTs and PaCBP confirmed the formation of protein complexes. Of the three PaCPTs, guayule transcriptomics analysis indicated that the PaCPT3 is predominantly expressed in stem and induced by cold-stress, suggesting its involvement in NR biosynthesis. The comprehensive analyses of these PaCPTs and PaCBP here provide the foundational knowledge to generate a high NR-yielding guayule.